2023
DOI: 10.1002/jex2.77
|View full text |Cite
|
Sign up to set email alerts
|

Cellular communication through extracellular vesicles and lipid droplets

Abstract: Cellular communication is essential for effective coordination of biological processes. One major form of intercellular communication occurs via the release of extracellular vesicles (EVs). These vesicles mediate intercellular communication through the transfer of their cargo and are actively explored for their role in various diseases and their potential therapeutic and diagnostic applications. Conversely, lipid droplets (LDs) are vesicles that transfer cargo within cells. Lipid droplets play roles in various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 167 publications
0
10
0
Order By: Relevance
“…The first mention of EVs was from Wolf P. in 1967, who obtained a pellet of EVs via the ultracentrifugation of platelet-poor plasma [ 15 ]. Later, it was shown that all cells release different types of EVs into the extracellular environment and participate in intercellular communication [ 16 ]. The initial classification of EVs was based on mechanisms of intracellular secretion and was categorized into three groups: (1) exosomes (diameter: 40–150 nm), which are secreted after the fusion of multivesicular bodies with the cell membrane; (2) microvesicles or ectosomes (diameter: 100–1000 nm), which are formed by budding from the plasma membrane into the intercellular space, and (3) apoptotic bodies (100–5000 nm), which are formed during apoptosis [ 17 ].…”
Section: Biogenesis and Classification Of Evsmentioning
confidence: 99%
“…The first mention of EVs was from Wolf P. in 1967, who obtained a pellet of EVs via the ultracentrifugation of platelet-poor plasma [ 15 ]. Later, it was shown that all cells release different types of EVs into the extracellular environment and participate in intercellular communication [ 16 ]. The initial classification of EVs was based on mechanisms of intracellular secretion and was categorized into three groups: (1) exosomes (diameter: 40–150 nm), which are secreted after the fusion of multivesicular bodies with the cell membrane; (2) microvesicles or ectosomes (diameter: 100–1000 nm), which are formed by budding from the plasma membrane into the intercellular space, and (3) apoptotic bodies (100–5000 nm), which are formed during apoptosis [ 17 ].…”
Section: Biogenesis and Classification Of Evsmentioning
confidence: 99%
“…LD proteomes are understood to be dynamic in nature, but with the limited availability of LD proteome data, a better understanding of how these changes occurs is still to be established (27,28). Very recently the LD proteome has been shown to be highly sensitive to bacterial LPS (29), however, the LPS changes driven in the LD proteome in this study have only a 17 protein overlap with those driven by viral RNA in our analysis, indicating that LD proteome changes are pathogen specific and likely to underpin specific functional capacity of the LD (Fig S7A ,B).…”
Section: Stat2 Rapid Proteomic Changes To Lds Following Viral Infecti...mentioning
confidence: 99%
“…Work in biomarker development has recently shifted focus to a class of nanoparticles (30–1000 nm) termed extracellular vesicles (EVs). EVs are released from all cell types into the local milieu and are also transported to distant sites via entry into the systemic circulation. They are believed to reflect the metabolic state of the cell of origin; thus, they can give insight into the overall health or physiological state of the host . Their size and composition are determined by their mode of biogenesis, for example; exosomes (50–150 nm) are formed within intraluminal vesicles (ILVs), arise from the endocytic pathway and are associated with the endosomal sorting complex required for transport (ESCRT), while ectosomes (100–1000 nm) are produced by direct budding from the plasma membrane. , Small (s)­EVs refer to classes of vesicles ranging from 50 to 200 nm in diameter, and we will use this terminology throughout this paper.…”
Section: Introductionmentioning
confidence: 99%
“…8−10 They are believed to reflect the metabolic state of the cell of origin; thus, they can give insight into the overall health or physiological state of the host. 11 biogenesis, for example; exosomes (50−150 nm) are formed within intraluminal vesicles (ILVs), arise from the endocytic pathway and are associated with the endosomal sorting complex required for transport (ESCRT), 12 while ectosomes (100−1000 nm) are produced by direct budding from the plasma membrane. 12,13 Small (s)EVs refer to classes of vesicles ranging from 50 to 200 nm in diameter, and we will use this terminology throughout this paper.…”
Section: Introductionmentioning
confidence: 99%